Deliberate save a rozmyślna parada obronna – kilka uwag o tłumaczeniu przepisów gry (w piłkę nożną) = Deliberate save or deliberate saving parade – few words about the translation of the laws of the game (in football) - Sobczak, Michał (Journal of Education, Health and Sport, 2015)
Sobczak Michał. Deliberate save a rozmyślna parada obronna – kilka uwag o tłumaczeniu przepisów gry (w piłkę nożną) = Deliberate save or deliberate saving parade – few words about the translation of the laws of the game (in football). Journal of Education, Health and Sport. 2015;5(11):678-684. eISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.35721 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%2811%29%3A678-684 http://pbn.nauka.gov.pl/works/685056 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport (null) 2391-8306 7 © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland. Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.11.2015. Revised 20.11.2015. Accepted: 30.11.2015. DELIBERATE SAVE A ROZMYŚLNA PARADA OBRONNA – KILKA UWAG O TŁUMACZENIU PRZEPISÓW GRY (W PIŁKĘ NOŻNĄ) DELIBERATE SAVE OR DELIBERATE SAVING PARADE – FEW WORDS ABOUT THE TRANSLATION OF THE LAWS OF THE GAME (IN FOOTBALL) Michał Sobczak Uniwersytet Kazimierza Wielkiego w Bydgoszczy Kazimierz Wielki University in Bydgoszcz Streszczenie Artykuł dotyczy tłumaczenia angielskiej wersji Przepisów gry w piłkę nożną na język polski. Przepisy gry opracowywane są przez FIFA w czterech językach: angielskim, hiszpańskim, niemieckim i francuskim, a pozostałe federacje zrzeszone w strukturach FIFA zobowiązane są do wykonania tłumaczenia Przepisów gry we własnym zakresie. Badania wykazały, że w pracach zespołu przygotowującego polską wersję Przepisów nie uczestniczą specjaliści (tłumacze, językoznawcy, filolodzy), co ma znaczący wpływ na popełnione w tłumaczeniu błędy translacyjne i usterki edytorskie. Na podstawie artykułu XI Przepisów gry – Spalony – omówiono szczegółowe niedociągnięcia powstałe podczas procesu tłumaczenia i obróbki tekstu. Analiza dowiodła, że błędy popełnione przez zespół opracowujący polską wersję językową związane są z interferencją międzyjęzykową, nieświadomością różnic systemowych między językiem angielskim i polszczyzną oraz niestosowaniem się do zasad normatywnych polszczyzny. Stwierdzono, że mimo, iż – zgodnie z wypracowanymi w polskim językoznawstwie teoriami przekładu – w procesie translacji nie muszą uczestniczyć zawodowi tłumacze – to konieczne jest tzw. kompetencja tłumaczeniowa, która obejmuje osiem aspektów przygotowania teoretycznego i osobowościowego osoby (zespołu) podejmującego się tłumaczenia. Konkluzję artykułu stanowi postulat o włączenie badań poświęconych przekładowi i językowi tekstów opisujących zasady rozgrywania dyscyplin sportowych do stosunkowo nowej gałęzi studiów językoznawczych – juryslingwistyki (lingwistyki prawa). Uznano także, że niezbędne jest włączenie do prac tłumaczeniowych – przynajmniej na płaszczyźnie kontrolnej – specjalistów z zakresu filologii i prawa. Słowa kluczowe: przepisy gry w piłkę nożną, tłumaczenie, język prawa, spalony. Summary The article describes the translation of English version of football rules into Polish. The game rules are presented by FIFA in four languages such as English, Spanish, German and French. The other federations affiliated to FIFA structures are required to translate the rules on their own. The studies have shown that linguistics specialists do not take an active part in the work of the team preparing the Polish version of the rules. It significantly impacts the translation causing a lot of translation and editorial errors. As an example an inaccurate translation of section XI of the game rules related to ’offside’ is described. The analysis has shown that errors made by the team preparing the Polish version of the rules are associated with interlingual interference, unawareness of systemic differences between English and Polish as well as non-compliance with the rules of normative Polish. It was agreed that although translation process does not have to be carried out by professional translators, translation competence is necessary. This in turn should include eight aspects of the theoretical and personal preparation of a team working on the translation. The article ends with the suggestion that research devoted to the language of the texts describing the sport rules should be included in a relatively new branch of linguistics studies – law linguistics. The work of philology and law experts should also be a part of the translation process. Key words: laws of the game in football, translation, language of the law, offside.